016. Case Report: Torsion of the Testicular Appendix in Pediatric - Akbar, Yundie Andrea; Balela, Naisya; Poerwasusanta, Hery (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p016, 2024)
Background : The testicular appendix or hydatidosa sessile Morgagni is a congenital disorder consisting of residual vestigial tissue of the mesonephric and Müllerian ducts1. Commonly it is attached to the testis and caput epididymis. Its presence can lead to twist around their own axis, causing acute scrotal pain. Case : A 8-year-old boy presented with gradual onset of left scrotal pain that worsened with movement and improved with rest. Other symptoms included scrotal swelling and redness/hyperemis. The ultrasonography examination revealed torsion of the testicular sinistra with mild hydrocele. During surgical intervention, testicular of the appendix torsion was found and appendiceal excision was performed. Conclusion: Torsion of thetesticulsr appendix is a benign condition that commonly affects prepubertal males. Its atypical symptoms of acute scrotal pain can lead to misdiagnosis as testicular torsion.